Rancang Bangun Aplikasi Pembelajaran Siswa SMA Berbasis Android - Elfasa, Zayed; Hariadi, Bambang; Amelia, Tan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The process of learning in high school from year to year changed so quickly and directly proportional with development of technology.  Process of development started from teaching which the source from educators (called teachers) who given to the high school students then changed to be “learn together”. This points are requirements of today students and past student is difference. The today students exist is being called “Digital Native” who students so close with gadget. The devices can be used by teachers and students for learning anytime and anywhere with mobile-based learning applications. Currently, mobile-based application for learning have not standard of learning. Standards learning consist by basic competencies, core competencies, and indicators as a reference of learning contents, exercises, and tasks. There is no standards in other learning mobile-based application it because making a learning application which have standards competencies to display learning contents, exercises, and tasks that can also be used for discussion via chatting. This application called “MoLearn Based in Android” and was created by collaboration with Musyawarah Guru Mata Pelajaran (MGMP) Biology and Geographic East Java Teams.Keywords: Application, High School Students, Mobile Learning, Standards Competencies